URGENSI KONSELING MULTIKULTURAL DI SEKOLAH - Elizar Elizar (Edukasi Lingua Sastra, 2018)
Every culture certainly has a different customs that will form the habit of a student in being. When the counselor and counselee met in the counseling process the counselor should first understand its cultural background.The counselling needed as solutions to the problems that arise. Morever faced conselors consist of student of different cultural background. Theefore, cross cultural counselor mus be aware ofthe studental values wich prssesses, second, crosss cultural counselor must be aware of the characteristics of counseling in general, third croos-cultural counselor must be aware of the influence of ethnicity and tthey must have attention to surroundings, fourth, croos-cultural counselor could not encourage one client to understanding the culture or te values owned counselors, and fifth cross-cultural counselor in implementing counseling must use ecletic approach. The counselor with a keen sensitivity better understand and appreciate the cultural bias between the counselor and counselee which is predicted to be able to direct the counselee to develop optimally.